Smart mobility innovations in regional transport services: a systemic view of triggers, approaches and outcomes in Japan - Trencher, Gregory; Hamano, Toshihiro; Shimono, Keisuke; Campfens, Jair; Duygan, Mert (Frontiers in Sustainable Cities, 2025)
IntroductionRegional urban and rural areas outside major metropolitan centres are facing escalating mobility challenges driven by declining socio-economic vitality and demographic shifts like population decline and ageing. Smart mobility innovations – including Autonomous Vehicles (AV), Demand-Responsive Transport (DRT), ridesharing and Mobility-as-a-Service (MaaS) – have attracted attention as potential solutions. Yet most scholarship on these innovations has focused on user acceptance or theoretical potential, offering limited empirical assessment of their actual problem-solving effectiveness. It consequently remains unclear whether these smart mobility technologies can live up to lofty expectations about their benefits, especially in regional settings facing declining socio-economic conditions.Objective and methodWe examine the experiences of regional Japan, where declining ridership and revenue – triggered by population aging and shrinkage – are forcing the contraction of public transport services and threatening their financial sustainability. Drawing on evidence from questionnaires and interviews, we comparatively examine the challenges, approaches and outcomes of 67 smart mobility projects implemented in 65 cities, towns and villages across Japan. A key contribution lies in our application of a common, systemic perspective – grounded in systems mapping methods – to analyse transport challenges across larger and smaller municipalities.ResultsFindings show that both larger and smaller municipalities are grappling with broadly the same challenges despite vastly differing geographical conditions. Our structural analysis indicates that challenges consist of root causes (driver shortages, declining revenue, poor convenience, downscaling of transport networks) and symptoms (poor access). In terms of effectiveness at tackling these challenges, the analysis reveals a mixed picture. On the one hand, projects reported substantial success in improving convenience, reducing accessibility barriers for users, and filling gaps in transport networks. On the other hand, we find less success at ameliorating other root-cause problems, notably driver shortages and low profitability.DiscussionOur empirics suggest that smart mobility innovations do not provide a panacea for all transport challenges, particularly when macro-level demographic conditions such as population ageing and decline pose a structural impediment to their effectiveness. Japan’s experiences in dealing with the impacts of population ageing and associated socio-economic decline on regional mobility carry high instructive value for other countries facing similar demographic changes.